Transcorneal electrical stimulation therapy may have a stabilization effect on multifocal electroretinography for patients with retinitis pigmentosa - SEVİK, MEHMET ORKUN; ŞAHİN, ÖZLEM (My University, 2022)
Purpose: To assess the effects of transcorneal electrical stimulation (TES) on several measures of visual function in retinitis pigmentosa. Methods: This prospective, randomized, fellow-eye-controlled study includes 30 eyes of 15 patients with retinitis pigmentosa. Each patient\"s eyes were randomly selected as treatment (TE) and control eye (CE), and 30 minutes/week TES was applied for 6 months. Patient evaluations were performed before and after TES, including comprehensive ophthalmological examination, visual fields, full-field and multifocal electroretinography, microperimetry, and optical coherence tomography. All parameters were compared before and after TES and between TE and CE. Results: After TES, the mean signal amplitudes in multifocal electroretinography were stabilized in TE. The mean signal amplitudes in CE decreased in every ring, reaching significance in the fifth ring (847.15 +/- 393.94 and 678.77 +/- 282.66 nV, P = 0.039, before and after TES, respectively). The changes in the mean signal amplitudes of TE and CE were -0.38 +/- 295.53 and -185.15 +/- 332,62 nV in second (P = 0.046), 36.69 +/- 326.4 and -143.38 +/- 317,41 nV in fourth (P = 0.028), and -17.46 +/- 333.07 and -168.38 +/- 297,14 nV in fifth rings (P = 0.046), respectively. The decrease in the mean signal amplitudes between 2 degrees and 20 degrees midperipheral retina was significantly less in TE (-33.59 +/- 225,1 nV) than CE (-205.56 +/- 345.1 nV) (P = 0.011). There were no significant changes in other parameters. Conclusion: The progression in multifocal electroretinography might be stabilized with TES. Further studies with larger sample sizes and a longer follow-up are needed to conclude that TES reduces retinitis pigmentosa progression.
Keywords: GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); retinitis pigmentosa; transcorneal electrical stimulation; neuroprotection; multifocal electroretinography; microperimetry; PRESERVES RETINAL FUNCTION; VISUAL-FIELD LOSS; FOLLOW-UP; MICROPERIMETRY; THICKNESS; PERIMETRY; GLAUCOMA; OCT